In-competition injuries and performance success in combined events during major international athletics championships - Edouard, P.; Navarro, L.; Pruvost, J.; Branco, P.; Junge, A. (Journal of Science and Medicine in Sport, 2021)
Objectives: To analyse the potential association between in-competition injuries and performance success (determined as "winning a medal") in combined events during international athletics championships. Methods: Newly incurred injuries were prospectively reported daily by the national medical teams and/or by the local organising committee physicians during 18 international athletics championships. Participation, climatic conditions and performance (medals) were collected retrospectively from the internet. Potential association between injury and performance success (win a medal) were analysed using an adjusted stepwise multiple regression and risk indicators presented as Odd Ratios (OR) (95%CI). Then, the proportions of injured competing athletes were descriptively presented among ranked and dropped-out, and medallist and non-medallist athletes. Results: A total of 799 athletes competed in combined events during the included 18 championships, of these 134 (16.8%) had at least one injury. An adjusted stepwise multiple regression analysis revealed that in-competition injury was significantly associated with lower odds of winning a medal (OR = 0.45 (95% CI 0.20-0.88)). The proportion of injured athletes was higher among the dropped-out than among the ranked athletes, and among non-medallists than medallists. Design: This was a total population design. Conclusions: During international athletics championships, being injured during a combined events competition was associated with lower odds of winning a medal. Injury prevention could contribute to improve performance success.